Status of Antibody Positivity and Antibody Titre After Six Weeks of Treatment With Levothyroxine in Primary Hypothyroid Patients - Islam, Abul Kalam Mohammad Aminul; Uddin, Mohammad Rafiq; Islam, Shiropa; Hasan, Mashfiqul (Jour Med Resh and Health Sci, 2023)
Background: Thyroglobulin antibody and thyroid peroxidase autoantibodies appear to be a secondary response to thyroid injury and are not thought to cause primary hypothyroidism themselves, although they may contribute to its development and chronicity. Anti-TPO-Ab, in particular, correlates well with thyroidal damage and lymphocytic infiltration. It is assumed that in Autoimmune Thyroid Disease (AITD), the injury process is persistently progressing unlike the NAITD group. There may be a difference of manifestation and response to treatment between the two goups. This part is not well estimated as yet and no definitive guideline about antibody status is as yet established. Methods: A prospective observational study included 99 primary hypothyroid patients, newly diagnosed on the basis of clinical suspicion and biochemical confirmation. The patients were 18-60 years of age and included both sexes. Both the Anti-TPO Antibody and the anti-TG antibody were measured before initiation and after six weeks of levothyroxine treatment. Results: 73 of the 93 patients who came at follow-up after 6 weeks were found anti-TPO (alone or along with anti-TG antibody) positive initially. After 6 weeks of treatment with levothyroxine, 70 (97.2%) of them remain anti-TPO antibody positive while 2 (2.8%) became anti-TPO antibody negative with p value of getting anti-TPO antibody negativity remaining non-significant (P=1.00). In case of anti-TG antibody, 55 of the 93 patients were positive before replacement (either alone or together with anti-TPO antibody). 49 (89.1%) of them remain positive after 6 weeks of treatment while 6 (10.9%) of the patients got anti-TG antibody negative with non significant p value (P=0.508). 77 of the patients were positive for either or both of the antibodies initially. All of them (100%) remain positive for either or for both of the antibodies after 6 weeks of treatment. Of the 16 patients who were antibody negative initially for both the antibodies, 3 (18.8%) got positive for at least one of the antibodies, while the other 13 (81.3%) remained negative for both the antibodies with insignificant p value(P=0.250). The median for anti-TPO antibody titre before treatment was 659 with interquartile range between 106-1000, with post treatment median titre declining to 446 and interquartile range being between 73-1000 with p value being significant (p<0.001) for both the median titre and the interquartile range. The median of anti-TG antibody titre was 77 and the interquartile range was between 20-381 before initiation of treatment while the median of the titre was 52 and the interquartile range was between 20-238 after 6 weeks of levothyroxine replacement, both being statistically significant (p<0.001) as revealed by Wilcoxon matched pair signed rank test. Conclusion: Though levothyroxine treatment in patients with antibody positive primary hypothyroid patients reduced the antibody titre significantly, there is no significant impact of treatment upon antibody positivity.